Consumer Protection Against Traditional and Dangerous Medicines in Indonesia - Indradewi, A.A. Sagung Ngurah; Sahid, Mualimin Mochammad (JUSTITIA JURNAL HUKUM, 2022)
Indonesia is a country that has abundant biological wealth. It encourages the rate of production of traditional medicines which is then followed by a high level of community culture towards the consumption of traditional medicines. Traditional medicine is an alternative medicine in addition to generic drugs sold in pharmacies. Many traditional medicines that circulate in the community. It turns out that not a few are included in the category of dangerous drugs. The formulation of the problem in this research is how to protect consumers when problems arise due to dangerous traditional medicines. This research uses normative juridical research methods, while the results show the Food and Drug Supervisory Agency (Badan Pengawas Obat dan Makanan /BPOM) is a agency that has the authority to give permits and has the right to withdraw traditional medicines. The role of BPOM is also to provide recommendations on policies, especially in the regulation of traditional medicines. It turns out that there are rules regarding traditional medicines still overlap between the Government and BPOM in terms of supervision and protection of the community so that there are still many violations. The rules regarding traditional medicine are not yet comprehensive. The task of BPOM supervises production and distribution. The sanctions for violations for traditional medicine producers are in Articles 60 to 63 of the UUPK, namely administrative sanctions, criminal sanctions, and additional criminal sanctions. Meanwhile, dispute resolution can be through litigation, non-litigation, or the Consumer Dispute Settlement Agency.